Research on the psychological resources of Ukrainians in overcoming war-induced distress, analysis of the experience of the civilian population in self-help - Сак, Леся; Малюк, Наталія (Psychosomatic Medicine and General Practice, 2025)
The search for effective ways to cope with distress is extremely important for maintaining the psychological resilience of the population in the context of modern warfare. The full-scale invasion is accompanied by many stressful factors that are difficult to adapt to and accept, such as: forced displacement, loss or injury of relatives and loved ones, destruction of housing and infrastructure due to constant shelling, uncertainty about the future and anxiety, and the lack of a safe environment. In such circumstances, the relevance of research on psychological resources that contribute to overcoming distress, as well as research aimed at studying effective self-help tools, becomes highly demanded and a priority. Studying these aspects will allow for a better understanding of which strategies are most effective and efficient in supporting and restoring emotional stability, and will contribute to the development of further recommendations for improving the emotional state and, accordingly, the mental health of the population in wartime.